Reengineering the corporation : - Hammer, Michael (HarperBusiness, 1993)
This book is about more than ideas, however. From their work with leading companies around the world, Hammer and Champy have learned how to make reengineering succeed. They lay out the approaches that have enabled such companies as Bell Atlantic, Taco Bell, and Hallmark Cards to reinvent themselves. They offer a vision of the reengineered corporation and a road map for companies to follow in getting there.